Correlation of song learning and territory establishment strategies in the song sparrow. - Beecher, M D (1994)
In a field study, we show that a young song sparrow (i) selects his songs from three or four older birds who have neighboring territories, (ii) preferentially learns song types that these tutor neighbors share, and (iii) ultimately sets up his territory next to, or replaces, one of these tutor neighbors. The consequence of this song learning strategy is that the young bird's song repertoire represents the "logical intersection" of the song repertoires of his tutor neighbors. We argue that this repertoire is optimally designed for mimicry (sounding like your neighbors) and for communication between neighbors (song sparrows address or reply to a neighbor with a song they share with that neighbor).